Estudio de prefactibilidad para la instalación de una planta de bebida de aguaje (Mauritia flexuosa) fortificada con sulfato ferroso - Romero Luciano, Karla Ximena (2024)
Currently, one of the great challenges in our country is the fight against anemia, and it is because of this health problem that the following prefeasibility study is proposed for a beverage fortified with ferrous sulfate oriented to people with mild anemia of socioeconomic levels B and C. In the study, it was determined that the target market will be Metropolitan Lima with an annual demand of 609 009 bottles of 300 mL each for consumption by people with mild anemia. At the macro level, the plant will be located in Metropolitan Lima. Likewise, the micro analysis determined that Lurin is the best option at the micro location level. The project engineering determined that ten operators and one machine will be needed for each stage of the production process. In addition, it was determined that an area of 270 ¿2 will be required. In the economic evaluation, indicators such as VAN were obtained with a value of 354 182,18 soles and an TIR of 29,77%, in which the economic TIR was higher than the COK whose value is 17,54%. Likewise, in the financial evaluation, a VAN was obtained with a value of 405 461,21 soles and an TIR of 36,13%, in which the financial TIR was higher than the COK of 17,54%. All this determined that the project is feasible and beneficial. Finally, in relation to the societal impact, indicators such as added value of 5 217 727,25 soles, capital density of 38 150,73 soles/inhabitant, labor productivity of 151 778,66 soles/inhabitant, capital intensity of 19,01% and a product-capital ratio of 5,2602 times the investment were obtained.